MAHASISWA SEBAGAI PENUNJANG KEBERHASILAN PEMBERIAN ASI - Aswita Amir; Chaerunnimah Chaerunnimah; Hj. Fatmawaty Suaib (Media Gizi Pangan, 2023)
Current counseling in health services does not involve other families, so mothers often do not receive support. Family support plays an important role in the success of breastfeeding. Counseling provided to mothers and families will increase knowledge and support for successful breastfeeding of their babies. Counseling can be done by a breastfeeding counselor at a health service. The performance of breastfeeding counselors is not optimal due to lack of work motivation caused by lack of financial support, lack of supervision, excessive workload due to the absence of special assignments as counselors. Students who are prospective health workers have good potential if guided to become counselors. Fun Home Counseling is a counseling activity that involves mothers and all families in the house to increase knowledge and support so that coverage of breastfeeding can be increased and will prevent stunting in Makassar City. To determine the effect of counseling on breastfeeding practices in Makassar City. This research is a pre-experimental research in the form of a post test group design. The population is all pregnant women in the Paccerakkang and Sudiang Raya Community Health Center working areas. The samples were mothers in the third trimester of pregnancy, permanent residents in the research area and participating in all counseling activities. The number of respondents in both groups was 16 people, but those who followed until the baby was 1 month old were 11 people in the counseling group and 14 people in the counseling group. The effect of counseling on breastfeeding practices using the Chi Square Test. There are no differences in employment, maternal nutritional status, number of parities, place of delivery, delivery process, Early Breastfeeding Initiation ((MD), breastfeeding assistance, postnatal intake, and intake at 14 days of age but different in breastfeeding at 1 months in counseling and counseling groups.